2022
DOI: 10.1039/d2na00092j
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering a glucose oxidase nanosensor for near-infrared continuous glucose monitoring

Abstract: Single-walled carbon nanotubes (SWCNTs) emit photostable near-infrared fluorescence that is conducive for optical glucose monitoring. Such SWCNT-based optical sensors often require the immobilization of proteins that can confer glucose selectivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The authors suggested direct reversible doping of nanotube surface defects, mediated by molecularly adsorbed oxygen, as a mechanism for the observed optical modulation. A subsequent study from the same group used bioconjugation reactions to outfit GOx with pyrene moieties that can anchor the enzyme to the nanotube surface through π-stacking interactions . Several recombinant GOx variants were anchored on nanotube surfaces and screened for their optical responses to glucose, which led to the identification of a variant that produced optical modulations with single milli-molar sensitivity, a feat the authors attribute to the oriented enzyme loading facilitated by pyrene binding.…”
Section: Cnm Fluorescent Probe Applicationsmentioning
confidence: 99%
“…The authors suggested direct reversible doping of nanotube surface defects, mediated by molecularly adsorbed oxygen, as a mechanism for the observed optical modulation. A subsequent study from the same group used bioconjugation reactions to outfit GOx with pyrene moieties that can anchor the enzyme to the nanotube surface through π-stacking interactions . Several recombinant GOx variants were anchored on nanotube surfaces and screened for their optical responses to glucose, which led to the identification of a variant that produced optical modulations with single milli-molar sensitivity, a feat the authors attribute to the oriented enzyme loading facilitated by pyrene binding.…”
Section: Cnm Fluorescent Probe Applicationsmentioning
confidence: 99%
“…Enzymatic glucose sensors have garnered significant attentions due to their selectivity, simplicity, and sensitivity. In recent studies, novel metal nanoclusters have been developed for the detection of the oxidation product of glucose by the glucose oxidase enzyme (GOx) [ 67 , 68 ]. Bovine serum albumin stabilized Au nanoclusters (BSA-AuNCs) and 1,2-bis [4-(3-sulfopropoxy)phenyl]-1,2-diphenylethylene (BSPOTPE) sodium were employed as the fluorescence detection probe and reference probe, respectively [ 69 ].…”
Section: Enzyme-based Sensing Platformmentioning
confidence: 99%
“…[14] Taking advantage of these attractive properties of SWCNTs and specifically the glucose recognizability of GOx, several SWCNT-based glucose nanosensors have been reported, with challenges including low synthesis scalability, sub-par colloidal stability, and poor reversibility. [7,[15][16][17][18] The synthesis of SWCNT-based nanosensors via biomolecule-SWCNT conjugation is typically accomplished through ultrasonication of polymer-SWCNT conjugates or through dialysis-based ligand exchange of biomolecule-SWCNT conjugates. [5,19] While probe tip sonication is quick and high-yielding, this method is typically deemed unsuitable for protein-SWCNT conjugation due to the denaturation of proteins under the high shear stresses induced by probe tip sonication.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their substrate‐specific enzymatic activity, enzymes can be used to rationally design nanosensors for a specific analyte of interest [14] . Taking advantage of these attractive properties of SWCNTs and specifically the glucose recognizability of GOx, several SWCNT‐based glucose nanosensors have been reported, with challenges including low synthesis scalability, sub‐par colloidal stability, and poor reversibility [7,15–18] …”
Section: Introductionmentioning
confidence: 99%